Penyelesaian Perkara Dengan Pendekatan Restorative Justice Dalam Pelaksanaan Tugas Di Direktorat Pamobvit Polda Maluku Di Wilayah Objek Vital - Manawan, Jzeron Luy; Supusepa, Reimon; Latupeirissa, Julianus Edwin (PATTIMURA Law Study Review, 2025)
In the Regulation of the Republic of Indonesia National Police Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice, which prioritizes justice for victims to make peace with the perpetrators in carrying out their functions and duties as personnel of the Pamobvit Directorate of the Maluku Regional Police, which often encounters obstacles or conventional crimes in the Vital Object area or the work area of ​​the Pamobvit Directorate of the Maluku Regional Police. This paper aims to analyze and discuss the restorative justice approach for minor crimes in handling vital objects carried out by the Directorate of Pamobvit Polda Maluku, analyze and discuss the obstacles in implementing restorative justice in carrying out the duties of the Directorate of Pamobvit Polda Maluku for handling regional vital objects, and as one of the requirements for completing studies at the Faculty of Law, Pattimura University. Normative research method, namely obtaining data from the library in the form of documents, books, magazines and other literature related to writing. The sources of legal materials used are Primary legal materials, Secondary legal materials, and Tertiary legal materials and are used as legal material collection techniques and then legal material processing and analysis techniques through qualitative analysis, namely the data obtained is then systematically arranged to be analyzed qualitatively based on civil law disciplines to achieve clarity of the problems to be discussed. The results of the study indicate that the Restorative Justice approach for minor criminal acts in handling vital objects carried out by the Directorate of Pamobvit Polda Maluku and what obstacles are there in implementing Restorative Justice in carrying out the duties of the Directorate of Pamobvit Polda Maluku for handling regional vital objects, the scope of minor crimes, duties and authorities, settlement mechanisms, forms of settlement of minor crimes, obstacles faced by Pamobvit and concrete solutions for handling minor crimes by Pamobvit.